Socially rational agents in spatial land use planning: A heuristic proposal based negotiation mechanism. (November 2016) - Ghavami, Seyed Morsal; Taleai, Mohammad; Arentze, Theo
Abstract: This paper introduces a novel heuristic based negotiation model for urban land use planning by using multi-agent systems. The model features two kinds of agents: facilitator and advocate. Facilitator agent runs the negotiation according to a certain protocol that defines the procedure. Two roles are designated for advocate agent in the negotiation process: speaker and listener roles. Advocate agents act as a speaker on a regular basis and its role is to propose a modification of land use plan for the listener agents. The role of listener agent is to express his opinion about the proposed plan. The model also considers that the agents are socially rational in proposing and responding to the others. Social rationality is the rationality of interpersonal relations and social action; it describes that in social contexts, people do not only care about their own payoff, but also they care about others' payoff. In fact, this research also seeks to examine the link with social reasoning and use its insights to explore conflicts between individual and social concerns in an urban land use planning meeting. An illustrative example of the proposed negotiation process is performed on a real-world case study. The results of the study are presented and are compared with two other scenarios: non-collaborative scenario (purely selfish) and fully-collaborative scenario (purely altruistic). The results show that the proposed social rationality scenario is more realistic, and it has a better performance than the two other scenarios. Highlights: Urban spatial land use planning is simulated by using multi agent systems. A multi-actor heuristic negotiation mechanism is proposed for urban land use planning. The impacts of social parameters in spatial urban land use planning are investigated in the research. A non-stationary strategy is proposed for the agents to do proposals or respond to other agents' proposals.